Fuzzy Reliability Analysis of the COVID-19 Mortality Rate Using a New Modified Kies Kumaraswamy Model - Fathy H. Riad; Bader Alruwaili; Ehab M. Almetwally; Eslam Hussam (Journal of Mathematics)
In this paper, we developed a novel superior distribution, demonstrated and derived its mathematical features, and assessed its fuzzy reliability function. The novel distribution has numerous advantages, including the fact that its CDf and PDf have a closed shape, making it particularly relevant in many domains of data science. We used both conventional and Bayesian approaches to make various sorts of estimations. A simulation research was carried out to investigate the performance of the classical and Bayesian estimators. Finally, we fitted a COVID-19 mortality real data set to the suggested distribution in order to compare its efficiency to that of its rivals.